Ma’had al-JÄmi’ah: Synthesis of Islamic Boarding School and University - Al Muiz, Mochamad Nasichin; Assegaf, Abd. Rachman; Machali, Imam (IAIN Ponorogo, 2023)
This study aims to investigate the role of Ma'had al-JÄmi'ah in achieving the vision of UIN Sayyid Ali Rahamtullah Tulungagung and to determine the implementation of the synthesis between Islamic boarding school education and Islamic university in the education system. This research employed a qualitative approach. The setting was at Ma'had al-JÄmi'ah Sayyid Ali Rahmatullah Tulungagung. The methods for collecting data were interviews, observation, and documentation. Data were validated by data triangulation. Meanwhile, the data analysis used an interactive model employing collection, reduction, display, and verification. The results of the study show that (1) Ma'had al-JÄmi'ah takes a strategic role in achieving the vision of UIN Sayyid Ali Rahmatullah Tulungagung through cultural education as a support for academic education, namely Islamic boarding school education, (2) the implementation of the synthesis of Islamic boarding school and Islamic University at Ma’had al-JÄmi’ah of UIN Tulungagung according to Parsons cannot be separated from four functions ”“ Adaptation, Goal Attainment, Integration, and Latency as requirements in its sustainability. The theoretical contribution that is built is that the existence of Ma’had al-JÄmi’ah can run and develop on top of the system that is formed.